Tolerance and Social Facilitation in the Foraging Behaviour of Free‐Ranging Crows (Corvus corone corone; C. c. cornix). (27th August 2014) - Miller, Rachael; Schiestl, Martina; Whiten, Andrew; Schwab, Christine; Bugnyar, Thomas; Herberstein, M.
Abstract Social foraging provides animals with opportunities to gain knowledge about available food. Studies indicate that animals are influenced by social context during exploration and are able to learn socially. Carrion and hooded crows, which are opportunistic generalists with flexible social systems, have so far received little focus in this area. We combined observational and experimental approaches to investigate social interactions during foraging and social influences on crow behaviour within a free‐ranging population at Vienna Zoo, which included 115 individually marked crows. We expected the crows to be tolerant of conspecifics during foraging due to high food abundance. We predicted that social context would enhance familiar object exploration, as well as a specific foraging strategy: predation by crows on other species. We found that crows were highly tolerant of one another, as reflected by their high rates of cofeeding – where they fed directly beside conspecific(s) – relative to affiliative or agonistic interactions. Evidence for social facilitation – when the observer's behaviour is affected by the mere presence of a model – was found in both object exploration and predation behaviour. Specifically, crows touched the objects more frequently when others were present (whilst only approaching the objects when alone), and conspecifics were present more frequently during predation events involving the high‐risk target species. Evidence for enhancement during object exploration – where the observer's attention is drawn to a place or object by a model's actions – was not confirmed in this context. Our results highlight the role played by the presence of conspecifics across different contexts: natural foraging behaviour, familiar object exploration and a specific foraging strategy. To our knowledge, this is one of the first corvid studies aimed at teasing apart specific social influence and learning mechanisms in the field. These crows therefore make promising candidates for studying social learning and its consequences under naturalistic conditions.